Impact of completeness of revascularization in complex coronary artery disease as measured with the SYNTAX revascularization index: An SEEDS Substudy. (21st January 2017) - Xu, Bo; Bettinger, Nicolas; Guan, Changdong; Redfors, Björn; Yang, Yuejin; Li, Bao; Han, Yaling; Su, Xi; Yuan, Zuyi; Généreux, Philippe
Abstract : Objectives: We sought to study whether the level of completeness of revascularization as measured by the SYNTAX revascularization index (SRI) independently predicts adverse ischemic events after percutaneous coronary intervention (PCI) with second‐generation drug‐eluting stents (DES). Background: The SRI quantifies the proportion of revascularized myocardium. It has been shown to independently predict adverse ischemic events after PCI with first‐generation DES. Methods: Among 1, 900 patients enrolled in a registry to evaluate safety and effectiveness of everolimus drug‐eluting stent (SEEDS) for coronary revascularization, the SRI was calculated and available for 1, 851 patients. The patients were stratified into three groups according to the degree of revascularization (SRI = 100% [complete revascularization], SRI = 50 to <100%, and SRI <50%). Two‐year mortality and major adverse cardiac events (MACE) were compared between the groups. Results: The SRI ranged from 4–100%, with a mean of 85.4%. Complete revascularization was achieved in 1, 190 patients, while the SRI was 50% to <100% in 472 patients and <50% in 189 patients. Two‐year mortality and MACE rates were higher in patients with lower SRI. ROC analysis showed an optimal SRI cutoff of 85% for predicting the 2‐year mortality risk. An SRI ≥85% was associated with a similar risk of death to complete revascularization. The SRI independently predicted 2‐year mortality and MACE. Conclusions: The SRI predicts mortality and adverse ischemic events in patients with complex CAD who underwent contemporary PCI with second‐generation DES. Revascularizing ≥85% of the CAD burden was associated with a good prognosis and should be considered as a reasonable goal. © 2017 Wiley Periodicals, Inc.